<span>17<=3-2x<=21
subtract 3
14<=-2x<=18
divide by 2
7<=-x<=9
now mutiply whole inequality by -1, this will reveres the inequality
-7>=x>=-9
or -9<=x<=-7
so there are mistakes in the line
the corrected lines are
17 less than or equal to 3 - 2x and 3 - 2x less than or equal to 21 (line one)
14 less than or equal to -2x and -2x less than or equal to 18 (line two)
-7 greater than or equal to x and x greater than or equal to -9 (line three)</span>
Answer:
((2 x^2 + 1)^2)/(x^2)
Step-by-step explanation:
Simplify the following:
(2 x + 1/x)^2
Hint: | Put the fractions in 2 x + 1/x over a common denominator.
Put each term in 2 x + 1/x over the common denominator x: 2 x + 1/x = (2 x^2)/x + 1/x:
((2 x^2)/x + 1/x)^2
Hint: | Combine (2 x^2)/x + 1/x into a single fraction.
(2 x^2)/x + 1/x = (2 x^2 + 1)/x:
((2 x^2 + 1)/x)^2
Hint: | Distribute exponents over quotients in ((2 x^2 + 1)/x)^2.
Multiply each exponent in (2 x^2 + 1)/x by 2:
Answer: ((2 x^2 + 1)^2)/(x^2)
Each just has different amounts of 0s
Multiply the number of minutes in an hour(60) by 4.5
Answer: C
Step-by-step explanation:
We can use the expanding rule to get that one if the expressions is
(9x^2 + 2x - 7)x + (9x^2 + 2x - 7)(-4)